The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.3390/infrastructures3040057
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring the Impact of Groundwater Pumping on Infrastructure Using Geographic Information System (GIS) and Persistent Scatterer Interferometry (PSI)

Abstract: Transportation infrastructure is critical for the advancement of society. Bridges are vital for an efficient transportation network. Bridges across the world undergo variable deformation/displacement due to the Earth’s dynamic processes. This displacement is caused by ground motion, which occurs from many natural and anthropogenic events. Events causing deformation include temperature fluctuation, subsidence, landslides, earthquakes, water/sea level variation, subsurface resource extraction, etc. Continual def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 37 publications
(39 reference statements)
0
9
0
Order By: Relevance
“…The PSInSAR tech nique is widely ap plied in the Earth sciences. Ex am ples in clude as fol lows: tec tonic ac tiv ity (Massironia et al, 2009;Antonielli et al, 2016), hydrogeological problems re lated to wa ter ex trac tion (Declercq et al, 2005;DePrekel et al, 2018), vol ca nic erup tions (Ferretti et al, 2008), seis mic ity pat tern anal y sis (Lagios et al, 2012), mea sure ments of dis place ments caused by earth quakes (Ishitsuka et al, 2015), and min ing-in duced ground de for ma tion mon i tor ing (Huang et al, 2019).…”
Section: Psinsar Techniquementioning
confidence: 99%
“…The PSInSAR tech nique is widely ap plied in the Earth sciences. Ex am ples in clude as fol lows: tec tonic ac tiv ity (Massironia et al, 2009;Antonielli et al, 2016), hydrogeological problems re lated to wa ter ex trac tion (Declercq et al, 2005;DePrekel et al, 2018), vol ca nic erup tions (Ferretti et al, 2008), seis mic ity pat tern anal y sis (Lagios et al, 2012), mea sure ments of dis place ments caused by earth quakes (Ishitsuka et al, 2015), and min ing-in duced ground de for ma tion mon i tor ing (Huang et al, 2019).…”
Section: Psinsar Techniquementioning
confidence: 99%
“…Due to the high cost of sensors, only a few assets around the world are equipped with sitebased instruments, while the health-structural evaluation is mainly performed through visual inspections. [15][16][17][18] Inspection timelines are different for different countries and specific assets. For example, in the USA routine bridgeinspections are usually performed every 1 or 2 years, while underwater inspections take place every 6 years.…”
Section: Introductionmentioning
confidence: 99%
“…This makes MT-InSAR techniques an excellent tool for detecting deformations over built-up areas [29][30][31] and civil infrastructure. 15,18,[32][33][34] Recent studies have shown the feasibility of space-borne MT-InSAR techniques to provide accurate spatial information for building monitoring, [35][36][37][38][39][40][41][42][43][44] bridges, 16,45,46 dams, [47][48][49][50] railways [51][52][53][54] and other linear infrastructure, [55][56][57][58][59] demonstrating that remote-sensing data can be effectively utilised in combination with conventional ground-based monitoring systems, such as precise levellings and automated total stations. However, the information obtained from MT-InSAR analysis typically consists of a huge amount of data.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[26][27][28] Among the available MT-InSAR techniques, Persistent Scatterer (PS) Interferometry 29,30 is capable of extracting temporal series deformations for a high number of points located on buildings and structures. 31 The application of PS Interferometry to buildings, [32][33][34][35][36][37][38][39][40][41] archaeological sites, 42 bridges, [43][44][45] dams, [46][47][48] railways 49 and roadways 50 and the cross-validation of PS-InSAR-based measurements against GPS, [51][52][53][54] traditional levellings 36,38,[55][56][57][58] and other in situ instruments 46,[59][60][61][62] demonstrate the reliability of this approach for structural-health monitoring.…”
Section: Introductionmentioning
confidence: 99%